Speed management in Helsinki - Pasanen, Eero (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
Since early seventies, the number of traffic fatalities in the City of Helsinki has dropped dramatically in spite of the growth of the car mileage to twofold. By excluding the potential effects of all other changes in traffic, it has been evaluated that speed management has been the most important single factor behind this developement. At present, 30 kph speed limits exist on many down-town main streets with a traffic volume up to 30000 vehicles per day.